Visual resonance : fine art and 3D stereo pictoriality - Conradi, Ina (2021)
The paper will present art practice based research as perceptual, cognitive and interactive digital imaging, with focus on 3D stereo animated painting and virtual environments. An opportunity afforded to artist by the current research environment at the Nan yang Technological University, the School of Art, Design and Media, is providing the flexible venues for collaboration among the academia faculty from art and media and engineering school, along with collaboration from the local industries. The enthusiasm for painting and the magic of stereo are at the core of the write up.